Penerapan Peraturan Mahkamah Agung Nomor 1 Tahun 2020 Tentang Pedoman Pemidanaan Pasal 2 Dan Pasal 3 Undang-Undang Pemberantasan Tindak Pidana Korupsi Di Pengadilan Negeri Pekanbaru - Tri Novita Sari Manihuruk; Yusuf Daeng; Olivia Anggie Johar (Universitas Medan Area, 2022)
This study aims to find out the guidelines used by the panel of judges in dealing with criminal acts of corruption, especially acts that are subject to offenses under Article 2 and Article 3 of the Corruption Law based on PERMA Number 1 of 2020. Juridically, the PERMA is binding on Pekanbaru District Court Judges in making their decisions. . However, the facts on the ground show that there is still a disparity in sentencing by judges at the Pekanbaru District Court in passing their decisions on corruption crimes which are subject to articles 2 and 3 of the Corruption Law. The research method in this writing is a normative research method that is descriptive analysis using primary legal sources, secondary legal materials and tertiary legal materials then analyzed qualitatively using logical thinking in drawing conclusions which are carried out deductively. The results of the research show that the application of Supreme Court Regulation Number 1 of 2020 concerning Guidelines for Punishment of Articles 2 and Article 3 of the Law on the Eradication of Corruption Crimes in the Pekanbaru District Court has been properly implemented. This means that in determining the severity of the crime the Pekanbaru District Court judge considers sequentially the stages, including the following: categories of state financial losses or the country's economy; error rate, impact and profit; range of criminal convictions; aggravating and mitigating circumstances; criminal conviction; and other provisions related to criminal imposition